2017
DOI: 10.1001/jamaoto.2016.2771
|View full text |Cite
|
Sign up to set email alerts
|

Device Life of the Tracheoesophageal Voice Prosthesis Revisited

Abstract: Importance-Voice prosthesis (VP) device life is a limiting factor of tracheoesophageal (TE) voice restoration that drives patient satisfaction, health care costs, and overall burden. Historic data suggest that TE VPs have an average device life of generally 3 to 6 months, but these data are typically derived from small samples using only 1 or 2 devices.Objective-To reexamine current device life in a large, contemporary cancer hospital in the United States that uses a wide assortment of VPs. Main Outcomes and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 17 publications
(36 reference statements)
2
51
2
1
Order By: Relevance
“…Central and lateral leakage of fluids by the tracheoesophageal fistula is the most common and potentially life-threatening dysfunction. It might lead to aspiration pneumonia [ 24 , 25 , 26 ]. The average lifetime of a single Provox voice prosthesis is about 4–6 months, but there are individual variations of the time of exploitation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Central and lateral leakage of fluids by the tracheoesophageal fistula is the most common and potentially life-threatening dysfunction. It might lead to aspiration pneumonia [ 24 , 25 , 26 ]. The average lifetime of a single Provox voice prosthesis is about 4–6 months, but there are individual variations of the time of exploitation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…1a ). Recent clinical studies have shown a decreasing device lifetime of modern VPs from 3–5 to approximately 2 months [ 5 ]. This puts emphasis on the demand for more durable prosthetic materials, antibiofilm coatings or bioactive surfaces for VPs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,7 These studies have, however, been conducted in a time where primary TL was the gold standard in advanced larynx and hypopharynx cancer treatment. [9][10][11] In 2000, Op de Coul et al 4 published the long-term results of voice rehabilitation with the first Provox VPs in the Netherlands Cancer Institute. 8 This has, however, also led to an increase in salvage TLs after failed (C)RT, which have been associated with more TE wall (TEP tract)-related problems and possibly a lower device lifetime of VPs.…”
mentioning
confidence: 99%